Negative Mood Reduces Self-Referential Memory Effects in an Online Object Ownership Simulation - Mciver, Nicole (Department of Psychology, 2023)
The Self-Reference Effect (SRE) is a cognitive bias in which self-relevant stimuli are prioritised for processing. This bias allocates more attentional and encoding resources to selfrelevant objects making their memory traces more robust and easily retrievable. Research has repeatedly shown that self-owned and self-proximal objects benefit from this bias. However, little is known about the factors that impact the SRE. Emerging research suggests that emotion may attenuate the SRE. For instance, studies show that the salience of a self-related stimulus reduces when the stimulus is associated with negative self-referential information. However, there is limited research on how the SRE may be modulated by transient mood states. The major aim of the present study is to determine whether the SRE may be modulated by transient mood states. We investigated whether an induced negative mood state alters memory for self-related objects using an online emotion induction and shopping task. This task was selected because although SRE effects are robust in laboratory conditions, most studies rely on tasks with low external validity. All participants completed an online mood induction protocol (either negative or neutral mood induction). Thereafter, participants completed an online self-referencing object ownership task involving encoding (and subsequent recall) of self-owned, familiar other-owned, or unfamiliar other-owned everyday household shopping items. The group induced into a negative mood showed reduced memory recognition accuracy compared to the neutral mood group, with reduced memory for selfowned items. Further analyses revealed that negative mood interacted with both depression scores and object ownership to influence self-referential processing. Our results add to current SRE evidence and offer insights into how this bias can be influenced by both transient mood states and affective symptoms. Keywords: Self-reference, Object Ownership, Mood, Negative Emotion, Online.